Strategies to improve the mechanical properties of high-density polylactic acid foams. (January 2016) - Geissler, Bernd; Feuchter, Michael; Laske, Stephan; Fasching, Michael; Holzer, Clemens; Langecker, Günter R
In this study, different strategies to improve the mechanical properties of physically foamed high-density polylactic acid sheets were examined to produce polylactic acid foam sheets with tailor-made mechanical properties. The first part was the determination of the effect of different blowing agents (CO2 and N2 ) on the foam morphology. The second part of the study was the modification of the formulation. For this purpose, both a linear and a branching chain extender and a thermoplastic elastomer were used to improve the elongational properties (tensile modulus and strain at break) of the polylactic acid foam sheets. Additionally, the effect of the addition of cellulose fibers on the foam morphology and the mechanical properties was investigated. All experiments were carried out on a laboratory flat-film line. This extrusion line consists of a 30-mm single-screw extruder attached with a 250-mm flat sheet die. The results show a strong influence of the material formulation on the mechanical properties of the high-density foam sheets. Both the mechanical properties and foam morphology could be improved by the right material formulation. The addition of the thermoplastic elastomer leads to a better foam morphology and also to a reduced brittleness of the foam sheets. Furthermore, it could be demonstrated that cellulose fiber can be used as a nucleating agent for polylactic acid but causes a further decrease in the strain at break.